A Systematic Review: Does Land based Exercise Improve the Quality of Life in Patient with Knee Osteoarthritis? - Sabina Afifatuzzahra; Suryo Saputra Perdana; Amalia Nur Azizah (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
Quality of Life (QoL) is a crucial aspect of an individual's well-being, and Knee Osteoarthritis (OA) is a chronic degenerative disease that significantly impacts QoL. OA patients experience functional impairment, leading to difficulty and pain in activities such as standing, squatting, walking, and climbing stairs. Land-based exercise is a non-pharmacological intervention recommended for long-term knee pain, as it can improve muscle strength, relieve pain, and improve function. However, excessive exercise can worsen pain. This systematic review evaluates literature on land-based exercise interventions that show significant effects on QoL and decrease in knee pain for patients with knee OA. The review includes six publications with randomized controlled trials and experimental studies that examined the impact of land-based exercise on knee OA. The review focuses on exercises such as yoga, strengthening exercises, Tai Ji, and Wuxinqi Exercise. The review finds that land-based exercise has a positive impact on physical function, pain reduction, and quality of life for patients with knee OA. Three publications with yoga and Wuxinqi Exercise showed significant results in pain management, increasing knee strength, and reducing pain in knee OA patients. The review concludes that land-based exercise is an appropriate intervention for people with knee OA related to pain and functional impairment.